The Contributions of Heleieth Saffioti to the Analysis of Domestic Work in Brazil - Gomes da Costa, Renata; Soares Vieira, Monique (Pontifícia Universidade Católica de São Paulo, 2021)
This article seeks to present the contributions of Heleieth Saffioti to the analysis of the function and nature of domestic work under capitalism. For that purpose, we study Saffioti’s principle works and we connect them to Marx’s debate on the configurations of work in capitalist society, especially the debate on productive and unproductive work. Saffioti defines domestic work as a non-capitalist work activity paid with the personal income of the family and/or the individual employer and having as its principle function the reproduction of the labor force.